Low-lying agricultural peatland sustainability under managed water regimes - Dawson, Quentin L. (Cranfield University, 2006)
The combined effects of ditchwater management regime and sub-irrigation spacing on water table fluctuation have been investigated for two low lying agricultural peatlands in England, West Sedgemoor in the Somerset Moors and Methwold Fen in the Norfolk Fenlands. The consequence of the resulting soil moisture regimes for microbially mediated mineralisation of soil organic matter has been examined on peat samples collected from the upper metre of peat profile from these two test sites. It is shown that sub-surface tile spacing has a strong influence on the transference of ditchwater regime to the mid-tile point in the field. Where sub-irrigation spacing is greater than 40 m the mid-point water table falls to similar levels experienced without any form of sub-irrigation intervention. Where sub-irrigation is at 10 m intervals the mid-point water table was found to be close to the water regime maintained in the ditches. Differences in field water-table level can lead to considerable variation in the matric potential experienced at different depths in the peat profile. As a consequence, peats at different stages of degradation (linked to depth) and under different land uses can exhibit variable physical and hydraulic properties. The von Post scale, which describes the degradation status of peats, has been linked to these physical properties but no simple model has been found between these properties and the von Post score. A good relationship has been found between saturated hydraulic conductivity and the van Genuchten alpha value which itself was related to the air entry value for all peats except the amorphous (unstructured) peat from Methwold fen. The water management regime, in conjunction with variations in physical and hydraulic properties of different peat types, influences the peat microbial community structure. At West Sedgemoor those peats that are wetter have predominantly anaerobic species, whilst those in drier environments have a greater proportion of aerobic species. At Methwold Fen the variable nature of the water management strategy appears to have homogenised the microbial community throughout the entire peat profile, resulting in more aerobic microbes in the deeper peat deposits. The type of microbial community and the degree of peat aeration dictate the efficiency with which soil organic matter is mineralised. Over the period October 2004 - July 2005 the rate of mineralisation in Methwold Fen peat samples averaged 0.40 g CO2-C m-2 hr-1 in saturated samples whilst in drier peat it averaged 0.72 g CO2-C m-2 hr-1. This clearly demonstrates that a wetter peat profile minimises the rate of microbially mediated organic matter mineralisation. Land use exerts an equally strong influence on microbial activity and can mask the true extent of soil organic matter mineralisation. Root exudates may offer an alternative source of organic carbon for microbial metabolic processes. Where the water table was maintained at 0.3 m below the soil surface respiration rates on grass covered West Sedgemoor peat samples was, at maximum, 1.46 g CO2-C m-2 hr-1 whilst on bare Methwold Fen peat samples it was less, at 1.06 g CO2-C m-2 hr-1. After removal of all surface vegetation the average rate of respiration switched, with Methwold Fen peats exhibiting a greater rate of organic matter mineralisation (7.27 µg CO2-C g soil-1 hr-1) than West Sedgemoor peats (3.8 µg CO2-C g soil-1 hr-1). Sub-irrigation modelling, using a drainage theory based water table model, can adequately simulate the soil water balance. Coupling the output of a comparable hydrological model (SWAP) with a process based model of nutrient dynamics(ANIMO) demonstrates that under future climate scenarios closely spaced subirrigation could reduce the mineralisation of soil organic matter to the atmosphere and reduce subsidence by up to 2mm year-1, thus reducing agricultural peatland contributions to greenhouse gas emissions and improving peatland sustainability1. Even partial aeration of a moist soil profile can lead to high rates of mineralisation. However, a combination of ditchwater management and sub-irrigation can, improve the sustainability of low lying peatlands if the management regime maximises the period of complete peatland inundation. 1 Sustainability being defined as maintenance and/or improvement of peat soil resource quality and/or longevity through the reduction of present day rates of subsidence and mineralisation.